Viral Vectors for Treating Diseases of the Nervous System - Latchman, David S. (International review of neurobiology ;, 2003)
Gene therapy offers considerable potential for the treatment of various incurable diseases of the nervous system. This volume describes a number of different viral vectors developed for achieving high efficiency gene delivery to the brain. Vectors described include those based on adenovirus, adeno-associated virus, Herpes Simplex Virus, lentivirus, and other retroviruses. It also discusses the potential application of such viruses in treating brain tumors, Parkinson's disease, and other diseases of the nervous system. * Provides up-to-date account of gene therapy approaches for incurable neurological disorders * Describes a range of gene delivery methods based on different viruses.